ChemInform Abstract: Straightforward Synthesis of Non‐natural L‐Chalcogen and L‐Diselenide N‐Boc‐protected‐γ‐amino Acid Derivatives. Issue 50 (10th December 2013) - Kawasoko, Cristiane Y.; Foletto, Patricia; Rodrigues, Oscar E. D.; Dornelles, Luciano; Schwab, Ricardo S.; Braga, Antonio L.
Abstract A simple, efficient and flexible route for the preparation of enantiopure selenium‐, telluro‐, and thio‐N‐protected‐γ‐amino acid derivatives (III) from glutamic acid is described.